Constructivist Learning Theory: A Framework for Student-Centered Instruction in the 21st Century Classroom - Aadil Hussain Mir; Mohammad Nazmul Alam; Akash Modi (CV. RADJA PUBLIKA, 2025)
The 21st-century classroom calls for pedagogical approaches that nurture critical thinking, creativity, collaboration, and problem-solving among learners. Constructivist Learning Theory offers a robust framework for achieving these goals by emphasizing active engagement, experiential learning, and knowledge construction rooted in real-life contexts. Grounded in the foundational theories of Jean Piaget and Lev Vygotsky, constructivism promotes student-centered instruction that values inquiry, exploration, and social interaction as central to the learning process. This paper explores the theoretical basis of constructivism and its practical application in modern educational settings. It discusses key instructional strategies such as project-based learning, inquiry-based learning, and collaborative learning, all of which align with the constructivist paradigm. Additionally, the paper highlights the evolving role of teachers as facilitators, the importance of learner autonomy, and the integration of educational technology as a cognitive tool. Using a qualitative methodology, the study relies on secondary sources, including peer-reviewed literature, educational policy documents, and theoretical analyses, to examine the relevance and impact of constructivist teaching in today’s classrooms. The findings support the view that constructivism provides a compelling framework for designing meaningful, learner-driven instruction that equips students with essential skills for success in the 21st century.